Respuesta :
Answer:
x=0.6, y=1.6
Step-by-step explanation:
Multiply the first equation by 2 and the second equation by 3, so we can cancel out the y terms:
4x+6y=12
21x-6y=3
Add these 2 equations together:
25x=15
x=0.6
Now, to solve for y, plug x back into any of the equations above:
2(0.6)+3y=6
1.2+3y=6
3y=4.8
y=1.6
Answer:
Below in bold.
Step-by-step explanation:
2x + 3y = 6 Multiply by 2:
7x – 2y = 1 Multiply by 3:
4x + 6y = 12
21x - 6y = 3 Adding:
25x = 15
x = 0.6. Substitute x = 0.6 into the first equation:
2*0.6 + 3y = 6
3y = 6 - 1.2 = 4.8
y = 1.6.